Reflection impulsivity and response inhibition in first-episode psychosis: relationship to cannabis use. Issue 10 (October 2013) - Huddy, V. C.; Clark, L.; Harrison, I.; Ron, M. A.; Moutoussis, M.; Barnes, T. R. E.; Joyce, E. M.
<x content-type="archive" xml:space="preserve">Abstract</x> Background People with psychosis demonstrate impaired response inhibition on the Stop Signal Task (SST). It is less clear if this impairment extends to reflection impulsivity, a form of impulsivity that has been linked to substance use in non-psychotic samples. Method We compared 49 patients with first-episode psychosis (FEP) and 30 healthy control participants on two forms of impulsivity measured using the Information Sampling Test (IST) and the SST, along with clinical and IQ assessments. We also compared those patients who used cannabis with those who had either given up or never used. Results Patients with FEP had significantly greater impairment in response inhibition but not in reflection impulsivity compared with healthy controls. By contrast, patients who reported current cannabis use demonstrated greater reflection impulsivity than those that had either given up or never used, whereas there were no differences in response inhibition. Conclusions These data suggest that abnormal reflection impulsivity is associated with substance use in psychosis but not psychosis itself; the opposite relationship may hold for response inhibition.